A Systematic Review of the Clinical and Economic Outcomes Associated with Guideline-recommended Food Provision Studies (P12-013-19). (13th June 2019) - Martinez, Joseph; Draime, Juanita; Gardner, Julia; Berman, Sarah; Chen, Aleda
Abstract: Objectives: Chronic disease prevalence is increasing, and healthcare costs of heart disease, diabetes (DM), and chronic kidney disease (CKD) exceed $600 billion annually. Adherence to dietary guidelines is low (<50%) despite positively impacting disease progression and clinical outcomes. Thus, the objective was to determine the clinical and economic impact of food-provision studies in heart disease, DM, and CKD. Methods: The protocol was registered in PROSPERO. Multiple databases, including MEDLINE/PubMed, were searched with pre-specified terms to identify food-provision studies from January 1, 2013-May 1, 2018 for heart disease, DM, and CKD. Identified articles underwent data extraction and appraisal. Since limited economic outcomes were included, published literature was utilized to determine the economic impact of key clinical outcomes. Results: Across diseases, 99 articles ( N  = 43, 175 patients) were included. Dietary adherence was considered "compliant" or ≥90% consistently. Significant clinical outcomes included 5–10% LDL reduction ( P  < 0.05), 4–11 mmHg systolic blood pressure reduction ( P  < 0.05), 30% reduction in metabolic syndrome prevalence ( P  < 0.05), 3–5% weight reduction ( P  < 0.05), lower CKD mortality rates, increased dialysis-free time (2 years: 50%, 5 years: 25%), with a calculated cost savings of 80.6–94.3% over meal costs due to lower dialysis rates. Literature review showed these outcomes would result in the following costs savings: lower CV event risk (20–30% reduction: $5–11 billion annually), saved hospitalization costs ($1–8 billion), and lower dialysis rates (25–50% reduction: $14–29 billion annually). In addition, DASH diet adherence in heart failure (HF) resulted in 16% fewer readmissions, 38-day shorter length of stay, and savings of $234, 096 per 100 HF patients (decreased readmissions) and $79, 425 per HF hospitalization. Conclusions: Providing nutritional support and meals to patients with chronic diseases significantly increases dietary adherence above 90% and allows patients to realize better disease control and fewer complications (CV events and dialysis). The US healthcare system may realize a significant reduction of $27–48 billion annually in healthcare costs with better control of chronic disease by providing meal therapy management. Funding Sources: Healthy Meals Supreme provided a grant for this project work.